Theology of Canon Law According to Professor Remigiusz Sobański - Gałkowski, Tomasz (Philosophy and Canon Law, 2022)
Remigiusz Sobański (†2010) was highly appreciated in the world of post-Council canon law studies. His research was published in many languages. Most of his scientific achievements were presented in the Polish language. For this reason, I reach for studies unknown to a wider community of canonists in order to present Professor Sobański’s views on theology of canon law, whose subject matter was a predominant topic of his scientific interests. I present the thematic scope of theology of canon law, its role in reference to fundamental issues of canon law, but also its inadequacy. Sobański thought that in order to fully illustrate the basic issues of canon law, theological approach should coexist with the legal one within one theory of canon law.